Can you read this chart? Assessing graph literacy competence and confidence calibration among Indonesian undergraduate health science students - Bustang Bustang; Garry Kuan (Jurnal Elemen, 2026)
Despite growing international interest in graph literacy among health science students, empirical evidence from Indonesian higher education remains scarce, particularly regarding the alignment between students' competence and their confidence in interpreting graphical health information. This study investigated graph literacy competence among undergraduate health science students at a public Indonesian university, examined the relationship between competence and confidence, and identified areas of difficulty. A cross-sectional design was employed with 78 undergraduate health science students from Years 1 to 4. The validated 13-item Graph Literacy Scale was administered alongside an item-level confidence rating task. Statistical and calibration analysis were used to examine performance, confidence, and their alignment. Results showed that students achieved a mean score of 5.31 (SD = 2.19) out of 13, substantially below international benchmarks. Calibration analysis revealed a non-significant mean calibration score, indicating adequate group-level metacognitive calibration. A weak-to-moderate positive correlation between competence and confidence was found (r = 0.34, p = .002), suggesting that more competent students tended to be more confident. These findings highlight the urgent need to integrate explicit graph literacy instruction into Indonesian health science curricula to better prepare future healthcare professionals for data-informed clinical practice.